THE EFFECTIVENESS OF THE ARCS LEARNING MODEL IN IMPROVING STUDENT LEARNING OUTCOMES IN ECONOMICS - Rahayu, Sri; Sutarni, Nani; Nofriansyah, Nofriansyah; Soffiatun, Soffi (Research and Development Journal of Education, 2025)
The ARCS model of learning is designed to improve students' attention, connect the content with their previous learning experiences, enhance their self-esteem, and foster satisfaction during the learning process. This study seeks to assess the impact of the ARCS model on students' academic performance in Economics. The research follows a quantitative approach using a Quasi-Experimental design. The participants included 40 students from Grade XI at SMA Nurul Falaah, split into two groups: an experimental class and a control class. The research tools consist of pretest and posttest assessments, alongside documentation. The findings reveal that: (1) the experimental class had an average score of 80.25%, which was higher than the control class's average of 78.60%; (2) the experimental class achieved a mastery rate of 85%, surpassing the Minimum Completion Criteria (KKM) of 75%; (3) there was a notable improvement in learning outcomes in the experimental class compared to the control class. Statistical analysis shows that the experimental class experienced a greater increase in learning outcomes. In conclusion, the ARCS model proves to be an effective method for enhancing students' learning outcomes in Economics.